Physical match performance and injuries in professional soccer before and after the COVID-19 break - Thron, M.; Härtel, S.; Woll, A.; Ruf, L.; Gross, T.; Altmann, S. (Science and Medicine in Football, 2021)
Purpose: To examine possible differences in physical match performance and the injury occurrence before and after the COVID-19 induced interruption of the 2019/2020 season of the German Bundesliga. Due to the interruption, matches and soccer-specific training were suspended for nine weeks, matches after the resumption of play occurred congested, and the playing situation changed, regarding, e.g., an increase to five substitutions. Methods: For this purpose, the 25 match-days before (pre) and the 9 match-days after (post) the COVID-19 induced interruption were examined regarding total distance, sprinting distance, average peak velocity, high-intensity distance, and injury occurrence. Results: Average peak velocity increased slightly for the comparison of pre and post with a small effect size (MD = 0.28 km/h, 95% CI: 0.11-0.45, p < 0.01, ES = 0.30, 95% CI: 0.12-0.48). There were no relevant differences in total distance, sprinting distance, high-intensity distance, and injury occurrence (0.11 = p = 0.82; 0.02= ES=0.15). Discussion: In terms of physical match performance and injury occurence results suggest the opportunity to recover and work on individual physical weaknesses during the interruption alongside with an increased number of substitutions was sufficient to compensate for the short soccer-specific preparation phase before the commencement of matches and the congested match schedule after the COVID-19 break.